2017
DOI: 10.1002/jcad.12148
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Trauma-Focused Therapies for Treating the Symptoms of Posttraumatic Stress Disorder

Abstract: This meta-analysis of 46 between-groups studies published between 1997 and 2015 detected treatment effects ranging from large to small when comparing trauma-focused therapies with no treatment (g = -1.05), supportive interventions (g = -0.91), other interventions (g = -0.57), and non-trauma-focused cognitive behavior therapies (g = -0.08) for the treatment of posttraumatic stress disorder (PTSD). The independent random-effects models detected modest publication bias and a negligible influence of moderating var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 81 publications
3
25
0
Order By: Relevance
“…The findings from this meta‐analysis confirmed existing knowledge about the degree of effectiveness that can be associated with counseling and therapy interventions for treatment of PTSD symptoms. The mean effect across all studies was similar to those reported by Erford et al (2016) and Lenz et al (2017) when contrasting all interventions versus no‐treatment comparisons. Thus, this study provides additional evidentiary support for the notion that individuals who seek help from counseling professionals tend to experience greater mitigation of PTSD symptoms when compared with those who rely on existing coping strategies and social supports for recovery.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The findings from this meta‐analysis confirmed existing knowledge about the degree of effectiveness that can be associated with counseling and therapy interventions for treatment of PTSD symptoms. The mean effect across all studies was similar to those reported by Erford et al (2016) and Lenz et al (2017) when contrasting all interventions versus no‐treatment comparisons. Thus, this study provides additional evidentiary support for the notion that individuals who seek help from counseling professionals tend to experience greater mitigation of PTSD symptoms when compared with those who rely on existing coping strategies and social supports for recovery.…”
Section: Discussionsupporting
confidence: 84%
“…First, our sample of studies evaluating PTSD interventions yielded a large mean effect size, thus supporting Erford et al’s (2016) propositions related to the pluralistic efficacy for many approaches to promote recovery from traumatic experiences. However, some interventions, particularly those that implemented standardized treatment protocols (e.g., prolonged exposure and cognitive processing therapy), have historically yielded stronger effects when compared with eclectic, supportive, or treatment‐as‐usual approaches (Lenz et al, 2017). Moreover, the scope of evidence established by our small sample of studies per trauma type does not suggest a ubiquitous generalization of treatment effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast we have substantially less understanding about the personal characteristics, strengths, interpersonal variables, and social determinants that influence them. Consider the large body of evidence supporting the use of therapeutic intervention for treating the symptoms of posttraumatic stress disorder (PTSD; Blankenship, 2017;Lenz, Haktanir, & Callender, 2017). Narrative and quantitative syntheses of results from primary studies have resulted in some convincing depictions about the amount of PTSD symptom relief that can be expected.…”
Section: Investigating Diverse Outcome Types and Social Determinantsmentioning
confidence: 99%
“…Rather than conduct our own systematic reviews, we searched the SCOPUS database for the most recent metaanalysis of RCTs for each anxiety disorder and depression, yielding the following sources: Cristea et al (2017) for major depressive disorder (MDD); Cuijpers, Cristea, Karyotaki, Reijnders, and Huibers (2016) for generalised anxiety disorder (GAD), panic disorder, and social anxiety disorder; Olatunji, Davis, Powers, and Smits (2013) for obsessivecompulsive disorder (OCD); and Lenz, Haktanir, and Callender (2017) for post-traumatic stress disorder (PTSD). Original articles of the studies included in these metaanalyses were then retrieved.…”
Section: Study Selectionmentioning
confidence: 99%